Successful Treatment of Driveline Infection with Vacuum-Assisted Closure Therapy and Instillation Therapy - Kilo, Juliane; Dumfarth, Julia; Höfer, Daniel; Grimm, Michael (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background Driveline infection is a serious complication in left ventricular assist device (LVAD) patients. We report the case of a patient who was successfully treated by combining instillation and vacuum-assisted closure (VAC) therapy.Case Description A 65-year-old LVAD patient presented with recurrent driveline infection. Local therapy with VAC therapy in combination with instillation of polyhexanide was performed for 2 weeks. The patient remains free from infection for twelve months by now.Conclusion This case is the first to present the combination of polyhexanide instillation with VAC as treatment for driveline infection. This therapy may thus be an option for patients who lack any other surgical option.
Keywords: circulatory assist devices; wound infection; surgery; complications